Pemberdayaan Karang Taruna Dalam Meningkatkan Kepedulian Sosial Pemuda - Dapot Pardamean Saragih; Ratna Juwita (Jurnal Administrasi Karya Dharma, 2022)
Karang Taruna is a youth organization that functions as a forum for the younger generation to develop themselves, grow and develop on the basis of awareness and social responsibility from, by, and for the younger generation, which is oriented towards achieving social welfare for the community. This study aims to find out how the empowerment carried out by youth organizations in increasing youth social awareness in Sidomulyo Village.This research is a qualitative descriptive study. The subjects in this study consisted of the head of the youth organization, members of the youth group, the head of the Sidomulyo village and the people of Sidomulyo village. Data collection techniques used are observation, interviews, and documents with data analysis techniques, namely data reduction, data presentation and drawing conclusions or verification. The results showed of the study show that in empowering youth organizations in increasing youth social awareness did not go well, seen from the lack of organizational management, lack of human resource capacity, lack of available facilities and infrastructure and existing networks in the youth organizations of Sidomulyo village